Ocupações de mães de bebês pré-termos durante a internação e após a alta hospitalar - Menegat, Danusa (2020)
Introduction: Occupations refer to practical and intentional activities that allow people to act independently and acquire a sense of identity. The construction of a person's occupational identity is shaped, over time, by occupational experiences. Mothers of preterm babies face numerous challenges in their occupational performance, which can threaten the development of occupational identity as a mother. This theme is little explored in research. Objective: To identify the occupations of mothers of preterm babies in the contexts of hospitalization and hospital discharge, and to analyze their relationship with the process of construction of maternal occupational identity. Method: This is a qualitative, exploratory-descriptive study, using the Human Occupation Model (MOH) as a conceptual framework. Data were collected during the baby's admission to the Neonatal Intermediate Care Unit (NICU); in the first week and one month after hospital discharge, at the baby's consultation at the High Risk Follow-up Clinic at the same institution. Nine women participated, mothers of preterm newborns admitted to the NICU, graduating from the Neonatal Intensive Care Unit (NICU), from an institution located in the city of São Paulo. The following instruments were used: 1) Identification Form; 2) Diary of Occupations and 3) Semi-structured interview. For the analysis, the data from the interviews were recorded and the transcripts were subjected to thematic content analysis; the results found in the Occupation Diaries were distributed based on the definitions and classifications of occupations and activities presented by the American Association of Occupational Therapy (AOTA). Results: Occupations related to motherhood concern the care and interaction with the child, the preparation for the baby's discharge from the learnings at the NICU and the performance of the maternal role at home, with autonomy and responsibility, although receiving support family members. After discharge, occupational changes occur, mainly, taking precautions with a preterm baby, such as, for example, restrictions on visits and administration of the baby's medications without constant help from the team. From the interviews, five thematic categories emerged: Pregnancy; Birth of a preterm; Maternity in the face of the child's hospitalization: difficulties and limitations; Child hospitalization: facilitating aspects and Construction of maternal occupational identity. Still, the semi-structured interview allowed the identification of occupations related to motherhood, considered significant / important and satisfactory / pleasurable, in the mothers' perception, in the three moments of the research. During the baby's hospitalization, the participants considered the activities as significant and satisfactory: breastfeeding / offering milk, taking care of the child and observing the team. One week after hospital discharge, visit restriction was considered a significant activity; and being with the baby all the time generated satisfaction. One month after discharge, those activities considered significant and satisfactory were the activities related to the interaction; and the child's basic and health care, such as the treatment of gastroesophageal reflux and administering medication, which are only significant. Discussion: The study allowed to know the construction of the occupational identity of mothers of preterm babies from the identification of occupations that made sense to them and the changes experienced in this process. In addition, the hospital and home environment demanded changes and daily occupational choices that expressed the transformation in the occupational identity of the participants. The data reaffirm the maternity of the preterm child, as a private experience and permeated by environmental, social and emotional contexts in facing this new reality. Final considerations: The data obtained are similar to studies on the maternity of a preterm baby, however, the direction for Occupational Therapy brought a unique aspect to this research, since it pointed out the activities performed, related to motherhood from the perspective occupation, by mothers who start this role in an environment and with a baby “different” from what is naturally expected. In addition, the study contributes to the understanding of the construction of maternal occupational identity in the context of hospitalization of preterm babies and in the first days at home, using the MOH precepts, which can assist in the instrumentalization of Occupational Therapists for the practice with mothers, facilitating them to engage in activities that constitute the complex world of motherhood as an occupation.